1998
DOI: 10.1021/ja9725561
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dispersion of Ni2+ Ions via Chelate Ligands in the Preparation of Ni/SiO2 Materials. A XAFS Study

Abstract: The influence of the Ni deposition mode on the dispersion of Ni2+ precursors was investigated in the preparation of Ni/SiO2 catalysts. The coordination sphere of Ni complexes was mainly studied by XAFS spectroscopy in the initial step (dried samples) and after a vacuum activating treatment at 700 °C. Four modes of deposition were compared, two leading to supported silicate phases (exchange with ammine ligands and deposition−precipitation) and the other ones using the ethanediamine ligand (exchange and impregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 51 publications
7
54
0
3
Order By: Relevance
“…Table 2 and Fig. 6 reveal several important points from the comparison with the literatures [28][29][30][31][32][33][34][35][36][37]. The distance and the coordination number of the first shells (oxygen backscatterer) on Ni-M41 indicate the presence of hexacoordinated Ni 2+ 6c ions [29] in the TIE sample.…”
Section: Characterization Of Nickel Species Loaded On the Mesoporous mentioning
confidence: 68%
“…Table 2 and Fig. 6 reveal several important points from the comparison with the literatures [28][29][30][31][32][33][34][35][36][37]. The distance and the coordination number of the first shells (oxygen backscatterer) on Ni-M41 indicate the presence of hexacoordinated Ni 2+ 6c ions [29] in the TIE sample.…”
Section: Characterization Of Nickel Species Loaded On the Mesoporous mentioning
confidence: 68%
“…The dried impregnate is heat treated in air, called calcination, to convert the precursor into the desired metal oxide, optionally followed by a high temperature reduction treatment to obtain the metal in question. State-of-the-art studies at low Ni loadings and strong precursor-support interactions have revealed much insight into the interplay between metal, ligands, counterions and supports, and their impact on the activity, selectivity and stability of the final catalyst [13,16,17,19]. Moreover, these studies have yielded fundamental insight into the importance of liquid-solid interactions between precursor solution and support on the formation of poorly reducible mixed Ni phases like aluminates or phyllosilicates.…”
Section: Introductionmentioning
confidence: 99%
“…Besides metal precursor salts, organic complexing agents such as citric acid and nitrilotriacetic acid are often added to impregnation solutions. [9][10][11] Different metal chelate complexes can thus be formed in the impregnation solution depending on pH and concentration. Moreover, it has been shown that pH gradients can occur inside catalyst bodies after impregnation, which can be expected to influence the interaction between metal-ion complexes and the support surface.…”
Section: Introductionmentioning
confidence: 99%